Implementasi Program BimBel Membaca Terhadap Siswa Yang Berkesulitan Membaca di SDN 33 Cakranegara - Khairunnisa, Izzati; Hati, Intan Permata; Jannah, Fitriatul; Lu'luilmaknun, Ulfa (Rengganis Jurnal Pengabdian Masyarakat, 2025)
The Reading Tutoring Program (BimBel) is one of the work programs of Kampus Mengajar (KM) 8 at SDN 33 Cakranegara, conducted with the aim of assisting students who are unable or experiencing difficulties in reading. The activities began with observation and interviews carried out during the first week of the assignment to collect data and identify 19 students who were not yet proficient in reading. There were 4 students from various grade levels who showed improvement in their reading abilities. This program was implemented from Monday, October 14, 2024, to Friday, November 22, 2024, with a tutoring duration of 30 minutes daily. During the preparation phase, the KM 8 team conducted a needs analysis of the students and prepared engaging learning media. The implementation phase involved intensive tutoring by five team members. The results indicate that students participating in the Reading Tutoring Program experienced significant improvements in their reading skills, ranging from letter recognition to fluent reading. This program not only enhanced students' reading abilities but also boosted their confidence in learning. It can be concluded that the Reading Tutoring Program has a positive impact on students and supports teachers in the classroom learning process.